Exploring the Role of Animated Cartoons in Promoting Values and Social Skills in Children - Dharmik Chauhan (Golden Ratio of Social Science and Education, 2026)
International Animated cartoons have long been an integral part of childhood entertainment across the world. Globally, some popular cartoons such as Tom and Jerry, Mickey Mouse, Donald Duck, Popeye the Sailor, and Looney Tunes implicitly contribute to children’s social, emotional, and cognitive development. This study examines the international animated cartoons can nurture value, social skills, and emotional competencies among school children. For social learning, cognitive development, and narrative pedagogy, this study highlights the educational and developmental tool beyond entertainment. The purpose of the animated cartoons is to integrate value-based education. This study examines how storytelling, humour, conflict resolution, and character-driven narrative foster empathy, cooperation, and ethical reasoning in children. The positive character traits and prosocial behaviour depicted in cartoons can enhance children’s ability to navigate social interactions and emotional challenges. The integration of value-based education through animated cartoons focuses on formal education and supports holistic child development. The study advocates for a more conscious and purposeful use of animated cartoons in educational settings, aiming to harness their potential in promoting values, moral development, and social-emotional learning among school children in an engaging and accessible manner.